The Impact of STEM Education on Critical Thinking Skills: A Systematic Literature Review - Kurnia Padmawati; Kartika Ratna Pertiwi; Slamet Suyanto; Ayu Nawang Wulan (Postgraduate, University of Mataram, 2025)
This study aims to systematically examine and synthesize empirical evidence on the impact of Science, Technology, Engineering, and Mathematics (STEM) education on students’ critical thinking skills. A systematic literature review (SLR) was conducted following the PRISMA protocol by initially identifying 200 relevant articles from reputable databases, including Scopus, ERIC, and Google Scholar. Through a rigorous screening and eligibility process, 10 peer-reviewed studies published between 2015 and 2025 were selected for in-depth analysis. The results indicate that STEM-based learning consistently enhances students’ critical thinking skills, particularly through project-based learning, problem-based learning, and inquiry-based instructional approaches. The discussion highlights that the effectiveness of STEM education is strongly influenced by the quality of learning design, interdisciplinary integration, engineering design activities, and the use of higher-order thinking assessments. Differences in implementation quality, teacher competence, and learning contexts contribute to variations in outcomes. In conclusion, STEM education is an effective pedagogical approach for developing students’ critical thinking skills; however, its success depends on well-structured implementation and adequate teacher preparedness to support 21st-century learning demands